2019
DOI: 10.1080/19476337.2019.1653378
|View full text |Cite
|
Sign up to set email alerts
|

Application for novel electrochemical screening of antioxidant potential and phytochemicals in Cornus mas extracts

Abstract: Cornelian cherry (Cornus mas L.), a fruit found in Central Europe, is used as a traditional ingredient in fruit preserves. In this study, we analyzed seven cultivars of Cornelian cherry growing in Poland and the differences between them in sugar content, total polyphenol content, and total chlorophyll content. Moreover, we measured the antioxidant potential of Cornelian cherry extracts was also measured. Polyphenols were found to be highest in Słowianin, Wydubieckij and Jolico cultivars. The presented research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…DPPH inhibition capacity was investigated according to the procedure described by Szczepaniak et al [44]. The calibration curve was prepared using Trolox standard solution in concentrations of 100-1000 µM.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…DPPH inhibition capacity was investigated according to the procedure described by Szczepaniak et al [44]. The calibration curve was prepared using Trolox standard solution in concentrations of 100-1000 µM.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…The data collected on antioxidant properties of C. mas are in line with results of other studies. In the previous study, the authors indicated that Szafer had the highest antioxidant potential against ABTS, but poorer against DPPH radical [16]. Gąstoł et al [22] noted that mean ferric FRAP value for cornelian cherry juice was approximately 23.5 μmol Fe 2+ /mL, and de Biaggi et al [23] observed FRAP levels at 20.41 μmol Fe 2+ /g of fresh weight.…”
Section: Discussionmentioning
confidence: 97%
“…Extraction of test samples was done using the method described in previous study [16]. The fruit skin was cut to facilitate higher migration of phytocompounds to the extractant.…”
Section: Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition capacity of DPPH was investigated according to the procedure performed by Szczepaniak et al (Szczepaniak et al, 2019). A calibration curve was prepared using a Trolox standard solution.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%